Instrumental variables in psychology - Hanema, Hugo (Student Undergraduate Research E-journal!, 2017)
In the social sciences, it is often of great importance to clearly uncover causal relationships. However, many researchers are unaware of the issue of endogeneity which biases estimates of causal effects. The instrumental variable (IV)-approach solves endogeneity and can make a convincing argument for causality even with cross-sectional data, but has been under-utilized in the social sciences. This paper explains the IV-approach and provides an example of application of this method to the psychological research question of causality between self-esteem and depression. The main argument is that the IV-approach is applicable to and deserves to see more use in psychology.